Malignant peripheral nerve sheath tumor in the nasopharynx and oropharynx: a case report. Issue 1 (January 2020) - Gu, Wen-Jing; Chang, Peng-yu; Wang, Ling-Jing; Zhu, Wei; Zhou, Hong-Wei
Malignant peripheral nerve sheath tumor (MPNST) in the nasopharynx and oropharynx has not been reported. A 3-year-old boy was referred to hospital after experiencing intermittent inspiratory dyspnea for 3 years. Preoperative imaging showed that the lymph nodes were clear. Therefore, neck lymph node dissection was not performed during the operation. This could have reduced the collateral damage. Complete excision and radiotherapy were performed because of the pathological diagnosis of MPNST. Because of the high location of the tumor, we chose the transoral approach instead of the cervical approach, avoiding tracheotomy, and we effectively improved the quality of life of the child. A mass in the nasopharynx and oropharynx was diagnosed pathologically as an MPNST after surgery. The patient's inspiratory dyspnea was resolved. No recurrence was observed during a 3-year follow-up. After review of our case, we found that postoperative recovery in our patient was closely related to accurate preoperative imaging assessment, the choice of operation methods, thorough resection, and postoperative neoadjuvant radiotherapy. Prevertebral fascia acted as a barrier to surround the mass and prevented it from growing further toward the vertebral body, which was important for a good prognosis. Children undergoing tracheotomy often have long tube management and difficult extubation.